(untitled) (Progressive Agriculture, 2014)
AARONG dairy area of Pabna comprises a major part to meet the demand of milk and meat production in Bangladesh. Various diseases including surgical affections reduce the fitness, efficiency and productivity of cattle in this area. There is a need to investigate the occurrence of surgical diseases to take proper preventive measures. Therefore, the prevalence of surgical affections of cattle was studied in four Upazilas of Pabna from December 2012 to May 2013. A total of 2390 cattle from different households were included and surgical affections were recorded. The overall prevalence was 44.3% in stall feeding system, among which surgical affections were more prevalent in Sujanagar Upazilas (13.3%), and the highest prevalent surgical affection was foot diseases (8.2%) followed by navel ill (6.3%), myiasis (4.6%), arthritis, hernia and wounds (3.6%). Overall prevalence of surgical affections was slightly higher in female cattle in comparison to males The prevalence of navel ill (11.3%), foot disease (11.1%), hernia (6.1%) and horn affections (4.9%) were found to be higher in male. Whereas, myiasis (5.9%), upward patellar fixation (2.8%) were found to be higher in females. There is significant (P<0.01) difference in the prevalence of hernia, upward patellar fixation, horn affection, foot diseases and myiasis between male and female. It was also observed that cattle of 0-1 year was affected more frequently with surgical affections (18.7%) among which prevalence of navel ill (15.5%), hernia (8.3%), myiasis (5.4%) and foot diseases (5.3%) were higher. In addition, foot disease was more prevalent surgical affection in cattle of more than one year. Moreover, significant variation (P<0.01) was existed in the prevalence of upward patellar fixation, foot diseases, arthritis and wounds among three age groups. However, results of the present study indicate that there is a strong relation among the prevalence of surgical affections, sex and age of animals. Moreover, foot disease is a common occurrence in stall feeding cattle in Pabna. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19104 Progress. Agric. 24(1&2): 85 - 92, 2013